The Influence of Customer Relatonship Management (CRM) and Satisfaction Members Regarding Participation Decisions With Loyalty As an Intervening Variable in the TCI Group - Purnamasari, Dewi (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Cooperatives are one of the community financing organizations or institutions that have long been present in Indonesia. TCI Group presents institution finance non-bank as holding which licensed Cooperative that is The well -known Tri Capital Investama Services Cooperative with TC Invest, TCI Group with various line business in between his Aminin Tour and Travel, agency Asia ACademy and Bahaso education, Permata Hijau Housing, TCI Fam, Fundex and several line business other. With level competition between institution finance non-banks and banks are very tight, and competition from line similar TCI Group businesses, condition This make company For do breakthrough For can more innovate and attract members​ new. At the moment level participation active members​ Cooperative Tri Capital Investama and member services line still other businesses Enough low matter This because lack of members ’ trust. Study This aim For test what is customer relationship management and satisfaction member with loyalty as variable intervening influential significant to decision participation member. Study This is study quantitative with amount sample as many as 235 members in the Mojokerto and Kediri areas with taking sample use purposive sampling technique. Data analysis techniques using analysis PLS-SEM pathway, utilizing the SMART-PLS program Version 3.0 Research results stated Customer Relationship Management and satisfaction member influential significant to decision participation with loyalty as intervening variable.